The Penguin thesaurus - Fergusson, Rosalind (Penguin Reference, 2004)
With nearly 400,000 synonyms and antonyms, The Penguin Thesaurus is the most extensive, authoritative and modern wordfinder currently available. Its alphabetical arrangement of the headwords means that it is very easy to use.